The commitment of local authorities in building fortress against misappropriation of assets / Rozaiha Ab. Majid … [et al.] - Ab. Majid, Rozaiha; Basri, Siti Aisyah; Mohamed, Nafsiah; Ahmad, Khairiah (Universiti Teknologi MARA Cawangan Selangor, 2016)
Many local authorities use vision, mission and policy statements to communicate their attitude towards the threat of asset misappropriation among their officials. These statements are imperative to the local authorities for disclosing their responsibility in safeguarding assets and expressing their commitment towards maintaining the highest possible ethical value. In Malaysia, vision, mission and policy are developed and implemented by local authorities to, among others, deter misconduct and dishonesty by their officials. The purpose of this paper is to investigate the level of commitment in preventing misappropriation of asset from occurring. Upon reviewing all Malaysian local authorities’ official websites, the term integrity in vision, mission and policy statement are identified and analysed. The existence of the term integrity can be an indicator to demonstrate the level of commitment of local authority towards maintaining a responsible and respectable organisation. Results from the study indicate most of local authorities in Malaysia are not committed in the fight against fraud including misappropriation of assets because integrity is not emphasized in their vision, mission and policy statements.